MEDIA FRAMING OF THE PROTESTS AT THE FACULTY OF PHILOSOPHY IN ZAGREB - Đukić, Marina (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
Having in mind the presence of ideological media influence in the areas in which audiences do not have alternative ideological sources or personal experiences and taking into account the fact that evaluation and selection of news are led by certain ideological systems, this paper explores the main elements of journalistic ideology present in the media reporting about the protests at the Philosophy College in Zagreb. Media content analysis is applied on the sample of three online news portals Indeks.hr, Tportal.hr and Net.hr, in the period of two months. The analysis included 111 media texts. Based on the protest paradigm studies and framing theory, the main purpose of the research was to explore the presence of influence factors (concealed ones or direct) which caused to story be told in a certain way. Research showed the prevalence of moral, responsibility and conflict media frames. Through these frames the media put the main focus not on the solutions of the conflict, but on conflict and transfer of responsibility on different event actors which were directly or indirectly involved in the conflict, and on the ones who were not involved at all. Journalistic ideology had less influence on media content because of the absence of focus on elite sources of information and actors, although the unusual elements of the event were emphasized. The selection of the sources of information showed that in crisis situations like this one the protesters (formal and informal institutions linked with College riots) were not marginalized but obtained the majority of media space.
Keywords: news sources; Protest; media frames; social networking sites; ideology; JOURNALISTS